Direct comparison of the acute effects of lysergic acid diethylamide and psilocybin in a double-blind placebo-controlled study in healthy subjects - Holze, Friederike; Ley, Laura; Müller, Felix; Becker, Anna M; Straumann, Isabelle; Vizeli, Patrick; Kuehne, Sebastian Silva; Roder, Marc A; Duthaler, Urs; Kolaczynska, Karolina E; Varghese, Nimmy; Eckert, Anne; et al. (Neuropsychopharmacology (New York, N.Y.), 2022)
Growing interest has been seen in using lysergic acid diethylamide (LSD) and psilocybin in psychiatric research and therapy. However, no modern studies have evaluated differences in subjective and autonomic effects of LSD and psilocybin or their similarities and dose equivalence. We used a double-blind, randomized, placebo-controlled, crossover design in 28 healthy subjects (14 women, 14 men) who underwent five 25 h sessions and received placebo, LSD (100 and 200 µg), and psilocybin (15 and 30 mg). Test days were separated by at least 10 days. Outcome measures included self-rating scales for subjective effects, autonomic effects, adverse effects, effect durations, plasma levels of brain-derived neurotrophic factor (BDNF), prolactin, cortisol, and oxytocin, and pharmacokinetics. The doses of 100 and 200 µg LSD and 30 mg psilocybin produced comparable subjective effects. The 15 mg psilocybin dose produced clearly weaker subjective effects compared with both doses of LSD and 30 mg psilocybin. The 200 µg dose of LSD induced higher ratings of ego-dissolution, impairments in control and cognition, and anxiety than the 100 µg dose. The 200 µg dose of LSD increased only ratings of ineffability significantly more than 30 mg psilocybin. LSD at both doses had clearly longer effect durations than psilocybin. Psilocybin increased blood pressure more than LSD, whereas LSD increased heart rate more than psilocybin. However, both LSD and psilocybin showed comparable cardiostimulant properties, assessed by the rate-pressure product. Both LSD and psilocybin had dose-proportional pharmacokinetics and first-order elimination. Both doses of LSD and the high dose of psilocybin produced qualitatively and quantitatively very similar subjective effects, indicating that alterations of mind that are induced by LSD and psilocybin do not differ beyond the effect duration. Any differences between LSD and psilocybin are dose-dependent rather than substance-dependent. However, LSD and psilocybin differentially increased heart rate and blood pressure. These results may assist with dose finding for future psychedelic research.Trial registration: ClinicalTrials.gov identifier: NCT03604744.